Dakwah Nabi Muhammad terhadap Masyarakat Madinah Perspektif Komunikasi Antarbudaya - Ahmad Anas; Hendri Hermawan Adinugraha (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2017)
The purpose of this research is to know strategy and method propagation of Prophet Muhammad to society of Medina through intercultural communication approach. This type of research was used descriptive qualitative research with historical approach. The author conducted data collection by way of library reseach and documentation, then the author uses descriptive analysis method to analyze data about propagation strategy of Prophet Muhammad SAW in Medina through intercultural communication approach. The result of the research shows that the propagation strategy of the Prophet towards the people of Medina is by building mosque, creating new brotherhood relationship between Muhajirin and Ansor people, building cooperation and peace agreement, and forming Medina Charter as conflict resolution. Later, the Prophet’s propagation of the Medina community through the approach of intercultural communication in spreading the religion of Islam through personal, education, discussion, offer, mission and correspondence methods have been able to realize Islam rahmatan lil’alamin. The proof of the Prophet’s da’wah success is that almost the entire population of Medina is Muslim. This is a clear proof of the Islam truth and the empirical reality of the effectiveness of Prophet’s propagation using intercultural communication. Tujuan penelitian ini ialah untuk mengetahui strategi dan metode dakwah Nabi Muhammad terhadap masyarakat Madinah melalui pendekatan komunikasi antarbudaya. Jenis penelitian ini adalah penelitian kualitatif deskriptif dengan pendekatan historis. Penulis melakukan pengumpulan data dengan cara riset kepustakaan dan dokumentasi, kemudian penulis menggunakan metode deskriptif analisis untuk menganalisis data tentang strategi dakwah Nabi Muhammad SAW di Madinah melalui pendekatan komunikasi antarbudaya. Hasil penelitian menunjukkan bahwa strategi dakwah Nabi terhadap masyarakat Madinah adalah dengan cara membangun Masjid, menciptakan hubungan persaudaraan baru atara orang Muhajirin dan Ansor, membangun kesepakatan kerjasama dan perdamaian, dan membentuk Piagam Madinah sebagai resolusi konflik. Kemudian, dakwah Nabi terhadap masyarakat Madinah melalui pendekatan komunikasi antarbudaya dalam menyebarkan agama Islam melalui metode personal, pendidikan, diskusi, penawaran, misi dan korespondensi telah mampu mewujudkan Islam yang rahmatan lil’alamin. Bukti dari keberhasilan dakwah Nabi ialah hampir keseluruhan dari penduduk Madinah beragama Islam. Ini sebagai bukti nyata tentang kebenaran agama Islam dan realitas empiris akan efektifitas dakwah Rasulullah menggunakan komunikasi antarbudaya.